Representing instances: the case for reengineering conceptual modelling grammars. Issue 1 (2nd January 2019) - Lukyanenko, Roman; Parsons, Jeffrey; Samuel, Binny M.
ABSTRACT: While many conceptual modelling grammars have been developed since the 1970s, they share the general assumption of representation by abstraction ; that is, representing generalised knowledge about the similarities among phenomena in a domain (classes) rather than about domain objects (instances). This assumption largely ignores the fundamental role that instances play in the constitution of reality and in human psychology. In this paper, we argue there is a need for a grammar that explicitly recognises the primary role of instances. We examine the limitations of traditional class-based approaches to conceptual modelling, especially for modern information environments. We then explore theoretical and practical motivations for instance-based modelling, and show how such an approach can address the limitations of traditional modelling approaches. We conclude by calling for the engineering of instance-based grammars as an important direction for conceptual modelling research to address the limitations of traditional approaches, and articulate five challenges to overcome in such efforts.